2021
DOI: 10.3389/fmed.2021.761314
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Symptoms After Discharge of Patients Hospitalized Due to COVID-19

Abstract: Many patients who had coronavirus disease 2019 (COVID-19) had at least one symptom that persisted after recovery from the acute phase. Our purpose was to review the empirical evidence on symptom prevalence, complications, and management of patients with long COVID. We systematically reviewed the literature on the clinical manifestations of long COVID-19, defined by the persistence of symptoms beyond the acute phase of infection. Bibliographic searches in PubMed and Google Scholar were conducted to retrieve rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 54 publications
3
27
0
2
Order By: Relevance
“…The symptoms of long COVID were varied. First, there were some physical symptoms: fatigue [ 9 , 12 , 35 ], dyspnea [ 35 , 36 ], cough [ 35 , 36 ], loss of taste or smell [ 12 ], loss hair [ 9 ], fever [ 35 , 37 ], sleep disorder [ 38 ], joint pain [ 39 , 40 ], headache [ 41 ], spinal pain [ 42 ], muscle pain [ 39 , 43 ], diarrhea [ 44 ], and organ (heart, lungs, kidneys, liver, pancreas, and spleen) damage [ 45 ]. Second, there were some mental symptoms: insomnia, delirium, fear, and depression [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The symptoms of long COVID were varied. First, there were some physical symptoms: fatigue [ 9 , 12 , 35 ], dyspnea [ 35 , 36 ], cough [ 35 , 36 ], loss of taste or smell [ 12 ], loss hair [ 9 ], fever [ 35 , 37 ], sleep disorder [ 38 ], joint pain [ 39 , 40 ], headache [ 41 ], spinal pain [ 42 ], muscle pain [ 39 , 43 ], diarrhea [ 44 ], and organ (heart, lungs, kidneys, liver, pancreas, and spleen) damage [ 45 ]. Second, there were some mental symptoms: insomnia, delirium, fear, and depression [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, identification of a molecular profile in relation to long COVID-19 still needs to be further investigated. Even though several studies have evaluated the main symptoms of long COVID-19 ( Abdallah et al., 2021 ; Augustin et al., 2021 ; Darley et al., 2021 ; Fernández-de-Las-Peñas et al., 2021 ; Logue et al., 2021 ; Wu et al., 2021 ; Huang et al, 2021a ; Huang et al., 2021b ), none of them investigated the association of clinical manifestations with the immunoinflammatory profile of cytokines. Our study showed, for the first time, evidence for the existence of a long COVID-19-associated cytokine profile in a cohort of the Brazilian Amazon region.…”
Section: Discussionmentioning
confidence: 99%
“…They need close monitoring, even after discharge, as the ongoing systemic inflammation may lead to ventricular dysfunction and malignant arrythmia 46 . Persistent symptoms may include hypotension, tachycardia, palpitations, dyspnoea and arrhythmias 47 , 48 , 49 , 50 , with some requiring hospital readmission 51 . There are increased risks of incident cardiovascular disease, such as cerebrovascular disorders (stroke/transient ischaemic attacks), dysrhythmia (atrial fibrillation/sinus tachycardia), ischaemic heart disease (acute coronary disease/myocardial infarction/angina), thromboembolic disease (pulmonary embolism/deep vein thrombosis), heart failure, pericarditis, myocarditis, cardiac arrest and cardiogenic shock 49 , 52 , 53 , 54 , 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%